Pemanfaatan Mahar Oleh Suami Tanpa Izin Istri Perspektif Konpilasi Hukum Islam - Ariana Harahap; Ikhwanuddin Harahap (Jurnal El-Thawalib, 2022)
The use of dowry by husbands without the wife's permission in Labuhan Labo Village, Southeast Padangsidimpuan District is an interesting thing to study, which is generally dowry in the form of objects such as a set of prayer tools, rings, etc., to be given to the wife. However, in this study the dowry used is in the form of money or a plot of land used for a living, the need to pay fines, business, and others even though the dowry itself is the right of the wife where using it must be with the wife's permission. The formulation of the problem in this study consists of: 1. How is the use of the dowry used by the husband without the wife's permission in Labuhan-labo Village, Southeast Padangsidimpuan District? 2. What is the review of the compilation of Islamic law on the use of dowry by a husband without the wife's permission on family harmony in Labuhan-labo Village, Southeast Padangsidimpuan District? The research objectives are: 1.To determine the use of the dowry used by the husband without the wife's permission in Labuhan-labo Village, Southeast Padangsidimpuan District. 2. To find out the review of the compilation of Islamic law on the use of dowry by husbands without the wife's permission on family harmony in Labuhan-labo Village, Southeast Padangsidimpuan District. This type of research is field research (field research). This research is also empirical by using a descriptive qualitative approach. Data collection techniques in this study are interviews, observation and documentation. The results of this study are: 1. The reasons behind the use of dowry are due to several factors including: reasonable use to meet family income, pay debts, venture capital and consider it joint property. 2. As a result of the use of dowry, namely: lack of harmony in the family, quarrels or disputes and divorce occur. 3. Based on the Compilation of Islamic Law, the use of the dowry may only be done with the wife's permission. Because the dowry is the property of a wife which the husband may not use for its benefits except with the permission and pleasure of the wife.